The Cognitive Dimensions of the Dialectic between Hyperrealism and Conceptualism in Art and Their Reflections on Plastic Arts Educational Thought - Buraq Ali Ahmed Alawadi (Academia Open, 2026)
General Background Postmodern artistic movements introduced structural transformations in visual presentation and epistemological mechanisms. Specific Background Two distinct trends emerged: hyperrealism utilizing photographic simulation to reconstruct reality, and conceptualism prioritizing abstract ideas over material forms. Knowledge Gap Although dominating postmodern visual culture, their underlying tensions and pedagogical values remain insufficiently integrated within traditional, technique-driven instruction. Aims This study investigates the epistemological dimensions of the opposition between extreme materiality and philosophical abstraction, examining their reflections on modern art education. Results Utilizing a descriptive-analytical methodology on works by prominent artists, the analysis reveals that synthesizing visual realism with conceptual abstraction stimulates critical thought, perceptual literacy, and reflective interpretation. Novelty This research uniquely frames the dialectic between meticulously detailed reproduction and dematerialized intellectual concepts as a complementary epistemic foundation for producing meaning. Implications Pedagogical practices must transition beyond mechanical imitation to incorporate inquiry-based learning and digital media, cultivating learners capable of critically engaging with ongoing socio-technological shifts. Highlights: Analytical examination reveals extreme visual accuracy and philosophical abstraction function as complementary epistemic tools. Synthesizing technical mastery with intellectual meaning stimulates inquiry-based learning and advanced reflective interpretation. Integrating modern digital media into pedagogical strategies cultivates critical responses to socio-technological transformations. Keywords: Postmodern Aesthetic Movements, Photographic Simulation, Abstract Philosophical Meaning, Perceptual Literacy, Inquiry-Based Learning